Polypharmacy, inappropriate prescribing, and deprescribing in older people: through a sex and gender lens - Rochon, Paula A; Petrovic, Mirko; Cherubini, Antonio; Onder, Graziano; O'Mahony, Denis; Sternberg, Shelley A; Stall, Nathan M; Gurwitz, Jerry H (The Lancet. Healthy longevity, 2021)
Polypharmacy is very common in older adults and increases the risk of inappropriate and unsafe prescribing for older adults. Older adults, particularly women (who make up the majority of this age group), are at the greatest risk for drug-related harm. Therefore, optimising drug prescribing for older people is very important. Identifying potentially inappropriate medications and opportunities for judicious deprescribing processes are intrinsically linked, complementary, and essential for optimising medication safety. This Review focuses on optimising prescribing for older adults by reducing doses or stopping drugs that are potentially harmful or that are no longer needed. We explore how sex (biological) and gender (sociocultural) factors are important considerations in safe drug prescribing. We conclude by providing a practical approach to optimising medication safety that clinicians can routinely apply to the care of their older patients, highlighting how sex and gender considerations inform medication decision making.